2009
DOI: 10.3109/09638280903183811
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of functional electrical stimulation for the treatment of shoulder subluxation and shoulder pain in hemiplegic patients: A randomized controlled trial

Abstract: The results of our study have shown that applying FES treatment to the supraspinatus and posterior deltoid muscles in addition to conventional treatment when treating the subluxation in hemiplegic patients is more beneficial than conventional treatment by itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 22 publications
5
45
0
2
Order By: Relevance
“…[23] Similarly, in another study, the authors showed that NMES application did not affect shoulder pain, although it reduced shoulder subluxation. [17] Controversially, in another study, the VAS-pain scores were more improved in the NMES treatment group than control group. [24] In this study, we found that, although the SDQ scores decreased in the NMES group, VAS-pain scores decreased in both groups.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…[23] Similarly, in another study, the authors showed that NMES application did not affect shoulder pain, although it reduced shoulder subluxation. [17] Controversially, in another study, the VAS-pain scores were more improved in the NMES treatment group than control group. [24] In this study, we found that, although the SDQ scores decreased in the NMES group, VAS-pain scores decreased in both groups.…”
Section: Discussionmentioning
confidence: 95%
“…[15][16][17]21] A study including 40 acute hemiplegic patients with GHS (20 patients in each control and NMES groups) examined the effects of four-week NMES application to the supraspinatus and posterior deltoid muscles. [21] The authors assessed all patients at four weeks after stroke and, then, at 12 weeks after stroke.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Electrical stimulation of the supraspinatus and deltoid muscles has been investigated and has shown some promising results, although there are no long-term follow-up studies on the benefits of this 6,7,14 ; however, a Cochrane review looking at this did not support its use. 30 Shoulder taping has been suggested to provide analgesia in patients suffering shoulder pain secondary to hemiplegia, but the evidence is weak.…”
Section: Managementmentioning
confidence: 95%